MOF with hydroxynaphthoquinone as organic linker: molecular structure of [Zn(Chlorolawsone)(2)(H2O)(2)] and thermogravimetric studies - Salunke-Gawali, Sunita; Kathawate, Laxmi; Puranik, Vedavati G. (Journal of Molecular Structure, 2012)
Zinc complexes as MOF with hydroxynaphthoquinone as organic linkers are synthesized and characterized. The complexes Zn-1; [Zn(lawsone)(2)(H2O)(2)]center dot 3H(2)O and Zn-2; [Zn(chlorolawsone)(2)(H2O)(2)]center dot H2O, where lawsone is 2-hydroxy-1,4-naphthoquinone and chlorolawsone is 3-chloro-2-hydroxy-1,4-naphthoquinone, serve as hosts for adsorbed water molecules. nu(c=O) shows shift towards lower frequencies similar to 25 cm(-1) in Zn-1 and similar to 35 cm(-1) in Zn-2 in FTIR spectra. (HNMR)-H-1 shows upfield shift in Zn-1 and downfield shift in Zn-2 to the benzenoid ring protons. Bathochromic shift has been observed to the charge transfer band in UV-visible spectra of both complexes. The mass loss of adsorbed water molecules have been observed <100 degrees C in thermogravimetric (TG) studies. Three adsorbed water molecules are present in Zn-1, while one in Zn-2. X-ray diffraction studies of Zn-2 show, distorted octahedral geometry around Zn(II). The two chlorolawsone ligands are in plane with the metal, while water molecules are trans to this plane. Formation of MOF has been observed in the synthesis of Zn-2 with chlorolawsone as organic linkers. The structure is stabilized by O-H center dot center dot center dot O, C-H center dot center dot center dot O hydrogen bonding H-bonding along with Cl center dot center dot center dot pi interactions to form a beautiful MOF architecture. Zn(II) atoms along with organic ligand form a tetramer via O-H center dot O interactions. The shortest Zn center dot center dot center dot Zn distance is 5.04 angstrom. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: 3-Chloro-2-hydroxy-1; 4-naphthoquinone; MOF; Naphthoquinone; O-H center dot center dot center dot O hydrogen bonding; Vapochromic behavior; Zinc complexes

Single crystal X-ray structure of lawsone anion: evidence for coordination of alkali metal ions and formation of naphthosemiquinone radical in basic media - Salunke-Gawali, Sunita; Kathawate, Laxmi; Shinde, Yogesh; Puranik, Vedavati G.; Weyhermueller, Thomas (Journal of Molecular Structure, 2012)
2-hydroxy-1,4-naphthoquinone; Lawsone (Lw) is a natural compound found in henna leaves. The reaction of lawsone with `Na' metal (Lw-1), CH3COONa (Lw-2), NaOH (Lw-3), KOH (Lw-4), K2CO3 (Lw-5) and Tris(hydroxymethyl)aminomethane (Lw-6) were studied. Red orange solids obtained for Lw-1 to Lw-6 are characterized by Elemental Analysis, FTIR, (HNMR)-H-1 and EPR studies. The results reveal the coordination of alkali metals `Na' and `K' to lawsone anion. The single crystal X-ray structure of Lw-6 was solved and it crystallizes in triclinic space group P-1 with extensive hydrogen bonding network of C-H center dot center dot center dot O, N-H center dot center dot center dot O and O-H center dot center dot center dot O between cations and anions. Polycrystalline powder X-band EPR spectra of Lw-1 to Lw-5 shows signals similar to 2.004 at 133 K, while Lw-6 is EPR silent. The naphthosemiquinone (NSQ) radical formed in Lw-2 to Lw-5, is due to disproportion reaction of catechol and naphthoquinone. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: 2-Hydroxy-1; 4-naphthoquione; EPR; hydrogen bonding; Lawsone; Naphthosemiquinone radicals

Synthesis and molecular structure of a zinc complex of the vitamin K-3 analogue phthiocol - Kathawate, Laxmi; Sproules, Stephen; Pawar, Omkar; Markad, Ganesh; Haram, Santosh K.; Puranik, Vedavati G.; Salunke-Gawali, Sunita (Journal of Molecular Structure, 2013)
The complex [Zn(phthiocol)(2)(H2O)(2)]; 1, where phthiocol is 2-hydroxy-3-methyl-1,4-naphthoquinone, has been synthesized and characterized by elemental analysis, FT-IR, H-1 NMR, UV-vis spectroscopy, thermogravimetric (TG) analysis, electrochemical and single crystal X-ray diffraction studies. The v(C=O) stretch shifts to lower frequencies upon complexation of phthiocol to Zn2+. H-1 NMR spectra show an upfield shift of the benzenoid ring protons in 1. There is a bathochromic shift of the LMCT band in the UV-vis spectra of 1. Single crystal X-ray structure of 1 show distorted octahedral geometry around Zn2+. Two phthiocol ligands are in plane with the metal, while water molecules are trans to this plane. Coordination of deprotonated phthiocol ligands is `trans, trans' to Zn2+. Intra as well as intermolecular interactions are observed in 1. Molecules of 1 show three dimensional network through C-H center dot center dot center dot O and O-H center dot center dot center dot O interactions. Additional anodic peaks are observed in cyclic voltammogram of phthiocol ligand due to oxidation of reduced species formed during reduction. One-electron reduction of 1 is shown to be reversible and DFT studies define this redox event as ligand-centered. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: hydrogen bonding; Naphthoquinone; Phthiocol; Trans coordination; Vitamin K-3; Zinc complex

Molecular structures and biological evaluation of 2-chloro-3-(n-alkylamino)-1,4-napthoquinone derivatives as potent antifungal agents - Pawar, Omkar; Patekar, Ashwini; Khan, Ayesha A.; Kathawate, Laxmi; Haram, Santosh K.; Markad, Ganesh; Puranik, Vedavati G.; Salunke-Gawali, Sunita (Journal of Molecular Structure, 2014)
Derivatives of 2-chloro-3-(n-alkylamino)-1,4-naphthoquinone (1-alkyl: methyl; L-1, ethyl; L-2, propyl; L-3 and butyl; L-4) have been synthesized and characterized by elemental analysis, FT-IR, H-1 NMR, UV-visible spectroscopy, LC-MS and single crystal X-ray diffraction studies. Antifungal activity of L-1 to L-4 has been evaluated against Candida tropicalis, Candida albicans and Cladosporium herbarum. The intramolecular hydrogen bonding affects the N-H vibrational frequency in L-2 (3273 cm(-1)). The single crystal X-ray structure reveal that L-1 and L-3 crystallizes in triclinic P-1, whereas L-2 crystallizes in orthorhombic Pca2(1), space group. An extensive intra and intermolecular hydrogen bonding interactions were observed in L-1 to L-3 which leads to molecular association. Intramolecular N-H center dot center dot center dot O hydrogen bonding were observed in L-1 to L-3. Moreover pi-pi stacking interactions were observed between the quinonoid rings of L-1 and L-3, however no such interactions were observed in L-2. An electrochemical study showed molecular association of L-1 to L-4 in DMSO solution. Compounds L-1 to L-4 were found to be potent antifungal agents against all the three strains, especially against C. tropicalis. Amongst these promising antifungal candidates, L-1 showed better activity compared to the clinically administered antifungal drug Amphotericin B and Nitrofurantoin with MIC = 1.25 mu g ml(-1) and MIC = 0.025 mu g ml(-1) respectively against C. albicans. Structure and activity relationship (SAR) study suggest a LogP value of similar to 2.0 and the cyclic voltammetry studies reveals additional chemical processes for L-1, which exhibits maximum activity against all fungal strains. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Aminonaphthoquinone; Antifungal activity; LogP; Naphthosemiquinone; pi-pi stacking

Reaction between lawsone and aminophenol derivatives: synthesis, characterization, molecular structures and antiproliferative activity - Kathawate, Laxmi; Joshi, Pranya V.; Dash, Tapan Kumar; Pal, Sanjima; Nikalje, Milind; Weyhermueller, Thomas; Puranik, Vedavati G.; Konkimalla, V. Badireenath; Salunke-Gawali, Sunita (Journal of Molecular Structure, 2014)
Reaction between two bioreductive reactants lawsone (2-hydroxy-1,4-napthoquinone) and derivatives 2-aminophenol without catalyst is reported. The reaction between lawsone and 4-chloro-2-aminophenol leads to formation of red colored major product 1A:[2-[(5-chloro-hydroxyphenyl)amino]naphthalene-1,4-dione] and fluorescent orange colored minor compound 1B:[10-chloro-benzo[alpha]phenoxazine-5-one]. Molecular structure of 1A and 1B were determined by single crystal X-ray diffraction. Two mechanisms were proposed to the formation of red 1A and 1B. `Ortho-para' tautomeric equilibrium was observed in DMSO-d(6) solution in 1A, which was revealed by H-1, C-13 NMR and LC-MS studies. Molecules of 1A formed dimers via N-H center dot center dot center dot O interaction and polymeric chain of dimers was formed by OH center dot center dot center dot O interactions. Cl center dot center dot center dot Cl interactions were observed between the polymeric chains of dimers in 1A. Molecules of 1B show Cl center dot center dot center dot N interaction. Antiproliferative properties is studied for 1A-5A compounds (obtained by the reaction of lawsone with 2-amino-4-methylpheno1;2A, 2-aminopheno1;3A, 3-aminophenol;4A and 4-aminophenol;5A) and evaluated against two cancer cell lines, THP1 (human monocytic leukemia cells) and COLO205 (colorectal adenocarcinoma) and one normal cell line, HEK293T (human embryonic kidney). The values of 50% inhibitory concentration (IC50) of compounds 1A-5A was determined using XTT assay. The cytotoxic effects of compounds 2A and 3A were observed against COLO205 and compounds 4A and 5A on THP1 were observed to be higher in comparison to their effect on HEK293T cell lines. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Aminonaphthoquinone; Aminophenol; Benzo[alpha]phenoxazine; Cl center dot center dot center dot N interactions; Lawsone; pi-pi stacking interaction

First naphthosemiquinone complex of K+ with vitamin K3 analog: experiment and density functional theory - Kathawate, Laxmi; Gejji, Shridhar P.; Yeole, Sachin D.; Verma, Prakash L.; Puranik, Vedavati G.; Salunke-Gawali, Sunita (Journal of Molecular Structure, 2015)
Synthesis and characterization of potassium complex of 2-hydroxy-3-methyl-1,4-naphthoquinone (phthiocol), the vitamin K3 analog, has been carried out using FT-IR, UV-Vis, H-1 and C-13 NMR, EPR, cyclic voltammetry and single crystal X-ray diffraction experiments combined with the density functional theory. It has been observed that naphthosemiquinone binds to two K+ ions extending the polymeric chain through bridging oxygens O(2) and O(3). The crystal network possesses hydrogen bonding interactions from coordinated water molecules showing water channels along the c-axis. C-13 NMR spectra revealed that the complexation of phthiocol with potassium ion engenders deshielding of C(2) signals, which appear at delta = similar to 14.6 ppm whereas those of C(3) exhibit up-field signals near delta similar to 6.9 ppm. These inferences are supported by the M06-2x based density functional theory. Electrochemical experiments further suggest that reduction of naphthosemiquinone results in only a cathodic peak from catechol. A triplet state arising from interactions between neighboring phthiocol anion lead to a half field signal at g = 4.1 in the polycrystalline X-band EPR spectra at 133 K. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: C-13 NMR; DFT; hydrogen bonding; Naphthosemiquinone; Phthiocol; Vitamin K3

Targeting a chemorefractory COLO205 (BRAF V600E) cell line using substituted benzo[alpha]phenoxazines - Pal, Sanjima; Konkimalla, V. Badireenath; Kathawate, Laxmi; Rao, Soniya S.; Gejji, Shridhar P.; Puranik, Vedavati G.; Weyhermueller, Thomas; Salunke-Gawali, Sunita (RSC Advances, 2015)
Mutational activations of the oncogene BRAF (especially BRAF V600E) result in a poor prognosis for colon cancer patients and are associated with chemoresistance rendering them refractory to treatment. The development of novel bioactive compounds with specific targeting abilities under such conditions is an urgent need in drug discovery. In this report we synthesize and characterize three fluorescent benzo[alpha]phenoxazine compounds (10R-benzo[alpha]phenoxazine-5-one, 1B; R = Cl, 2B; R = CH3, 3B; R = H) and their anticancer activities are evaluated in a COLO205 cell line. All three compounds with a log P value around 2 were cell permeable. However, 2B and 3B showed specific cytotoxicity in a malignant COLO205 cell line with a BRAF mutation (V600E) in comparison to a non-malignant wild-type BRAF HEK293T cell line. From further cell-based assays (cell cycle analysis, DNA fragmentation and caspase activation), we conclude that 2B and 3B treatment-induced selective cell death by inducing cell cycle arrest at the G0/G1 phase and caspase-mediated apoptosis (activation of the intrinsic and extrinsic pathways) are present only in BRAF V600E COLO205 cells. Further studies in the drug discovery pipeline might help develop these benzo[alpha]phenoxazines as promising chemotherapeutics for such refractory mutated cancers.